Analisis Image Noise dan Nilai Dosis Radiasi Penggunaan Aplikasi Care Dose 4D dan Non Care Dose 4D pada Pesawat MSCT Siemens - Tito Aditya Resmana; Darmini Darmini; Sigit Wijokongko (Jurnal Imejing Diagnostik (JImeD), 2017)
Background : One effective technique is contained in a CT Scan to decrease the amount of radiation dose that is received in the use of automatic exposure control (AEC). AEC system of Siemens equipment is called Care Dose 4D. The research is based on unused of the application Care Dose 4D on CT Scan Imaging. The purpose of the research is to determine the differences of image noise and the differences of radiation doses (CTDI) using care dose 4D and Non Care Dose 4D in Siemens MSCT.Methods                 :The research  was quantitative  study with experimental approaches that is tested on four water phantom size type. Analysts data is done by statistical tests of Paired T-Test Samples to test the hypothesis and the level difference image information. In this statistical analysis is determined the level of confidence (level of Significance) with a value of α = 0.05.Results  :                On the using of Nasopharing protocol for children with 130 kV and 130 mAs parameters, using of Care Dose 4D has ability to decrease the image noise value is compared with non Care Dose 4D application. While the adult Nasopharing protocol with 130 kV and 220 mAs parameters, Care Dose 4D doesn’t provide enough impact in the reduction of image noise value if compared with conventional techniques or without using Care Dose 4D applications. Using of children nasopharing protocol application Care Dose 4D even increase radiation closes high enough value in CTDI vol that is 5,03 mGy, but using Nasopharing Care Dose 4D applications for adult can decrease radiation doses high enough value in CTDIvol, that is 2,64 mGy.Conclusion : On the use of children nasopharing protocol application Care Dose 4D even increase radiation closes high enough value in CTDI vol that is 5,03 mGy, while the adult Nasopharing using Care Dose 4D applications can decrease radiation doses high enough value in CTDIvol, that is 2,64 mGy.